A study of formation and growth of the anodised surface layer on cast Al-Si alloys based on different analytical techniques. (5th July 2016) - Zhu, Baiwei; Seifeddine, Salem; Persson, Per O.Å.; Jarfors, Anders E.W.; Leisner, Peter; Zanella, Caterina
Abstract: This paper aims to investigate the mechanisms of formation and growth of the anodised surface layer on Al-Si castings by applying different analytical techniques such as optical microscopy, scanning electron microscopy (SEM), scanning transmission electron microscopy (STEM), and X-ray computer tomography (X-ray CT) scanning. Three different Al alloys with various Si content (2.43%, 3.53% and 5.45%) were investigated. Si particle morphological modification by Sr addition, as well as directional solidification, was used to vary the microstructural coarseness in a controlled manner to study the influence of these parameters on the growth behaviour of the oxide layer. This study observed residual unanodised Al phases trapped beneath or between Si particles in the oxide layer. It was found, depending on the geometry and morphology of Si particles, that Al can be shielded by Si particles and prevented from oxidising. Graphical abstract: Highlights: Four mechanisms for enhanced knowledge on the anodising and oxide growth on cast Al-Si alloys are presented. The Al-Si eutectic plays a significant role in the growth and uniformity of the oxide layer. Residual unanodised Al is found in the oxide layer. Modification of Si particle morphology reduces the amount of unanodised Al, cracks and cavities in the oxide layer.